UJI AKTIVITAS ANTIINFLAMASI KOMBINASI DEKOKTA AKAR BELUNTAS (Pluchea indica L.) DAN INFUSA DAUN JAMBU BIJI (Psidium guajava L.) TERHADAP TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI KARAGENAN - Ersamukti Rahmatullah Achmad; Yuliet Yuliet; Lutfiana Kusumawati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Marsh fleabane roots (Pluchea indica L.) and guava leaves (Psidium guajava L.) are traditionally used as an anti-inflammatory. The research has been conducted with the aim of knowing the anti-inflammatory effect of the combination of decoction of Marsh fleabane  roots (Pluchea indica L.) and infusion of guava leaves (Psidium guajava L.), and also determining  the effective concentration of such combination. The research used artificial edema method in white rat's leg ( Rattus norvegicus) with the observation for 6 hours on the change of leg volume in white rat.  The measurement of white rat's leg volume used a pletismometer. The type of treatment was devided into 5 groups: negative control (Aquadest), positive control (Na Diclofenac), combination 1 (MFR 10% : IGL 8%), combination 2 (MFR 5% : IGL 5%), and combination 3 (MFR 8% : IGL 10%).  The data obtained were processed using One-Way ANOVA method with the result seen on the percent inhibition of inflammation resulting concentration of MFR 5%: IGL 5% amounting to 23.47%, and subsequently combined with a concentration of MFR 10% : IGL 8% and concentrations MFR 8% : IGL 10% respectively by the percent inhibition of inflammation by 20.70% and 13.75%.  The data obtained show the combination with a concentration of 5% : 5% have anti- inflammatory effect are better than the other combinations as well as comparable to the positive  control